2013
DOI: 10.1111/ajt.12393
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Intervention for Living Donor Psychosocial Outcomes: Feasibility and Efficacy in a Randomized Controlled Trial

Abstract: There are no evidence-based interventions to prevent adverse psychosocial consequences after living donation. We conducted a single-site randomized controlled trial to examine the postdonation impact of a preventive intervention utilizing motivational interviewing (MI) to target a major risk factor for poor psychosocial outcomes, residual ambivalence (i.e., lingering hesitation and uncertainty) about donating. Of 184 prospective kidney or liver donors, 131 screened positive for ambivalence; 113 were randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 68 publications
1
63
0
Order By: Relevance
“…New modalities including mindfulness-based stress reduction interventions, more frequent monitoring of mood symptoms post donation, and problem-solving strategies to address financial stressors potentially could help alleviate the stress of undergoing donor surgery. Additionally, interventions such as motivational interviewing to explore donor ambivalence, possibly related to social obligation as a motivation to donate, has resulted in improved outcomes in other donor populations (33). This may be especially valuable for donor advocates wishing to assist donors in assessing whether they have sufficiently considered the risks and benefits of donation, to balance feeling compelled to donate by societal values.…”
Section: Discussionmentioning
confidence: 99%
“…New modalities including mindfulness-based stress reduction interventions, more frequent monitoring of mood symptoms post donation, and problem-solving strategies to address financial stressors potentially could help alleviate the stress of undergoing donor surgery. Additionally, interventions such as motivational interviewing to explore donor ambivalence, possibly related to social obligation as a motivation to donate, has resulted in improved outcomes in other donor populations (33). This may be especially valuable for donor advocates wishing to assist donors in assessing whether they have sufficiently considered the risks and benefits of donation, to balance feeling compelled to donate by societal values.…”
Section: Discussionmentioning
confidence: 99%
“…17 Internet-based interventions effectively increase knowledge, behavior, and improve health across different patient populations. [33][34][35] For example, Dew et al's 36 Internet-based intervention improved psychosocial outcomes in transplant recipients and their families. Merion and colleagues 37 deployed an Internet-based educational intervention for US middleand high-school students that significantly increased their willingness to donate and join a deceased donor registry.…”
mentioning
confidence: 99%
“…Of note, literature suggests that donors who describe ambivalence at the time of donation are at higher risk for a poor psychosocial outcome [24][25][26]. Best practice explores the prospective donor's readiness, or stage of decision making, as a process: the psychosocial provider (and/or the ILDA) conducts repeat assessment of the prospective donor's desire to proceed after s/he has completed medical evaluation, and been educated about individualized risk profile and LDT expected outcomes [25].…”
Section: Methods Of Assessing Voluntary Status-intentionalitymentioning
confidence: 99%
“…Influences affecting voluntary status, in Valapour et al's work, ran along a continuum ranging from persuasion to coercion [2,17]. Studies have repeatedly shown that LDs with the highest degree of (presumably, external) pressure around decisionmaking also had the highest rate of regret, or at least 'unsureness' about whether they would choose to donate again [26][27][28].…”
Section: Pressured Decision Makingmentioning
confidence: 99%